2015
DOI: 10.1002/ajp.22515
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of the gut microbiome marks the end‐stage of simian immunodeficiency virus infection in wild chimpanzees

Abstract: Enteric dysbiosis is a characteristic feature of progressive human immunodeficiency virus type 1 (HIV-1) infection but has not been observed in simian immunodeficiency virus (SIVmac)-infected macaques, including in animals with end-stage disease. This has raised questions concerning the mechanisms underlying the HIV-1 associated enteropathy, with factors other than virus infection, such as lifestyle and antibiotic use, implicated as playing possible causal roles. Simian immunodeficiency virus of chimpanzees (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 65 publications
(134 reference statements)
0
26
0
Order By: Relevance
“…Over the past two decades, microsatellite analyses have been an integral part of studies of wild chimpanzees, providing insight into their evolution, population genetics, behavior, disease association and social structure (Barbian et al, 2018;Becquet, Patterson, Stone, Przeworski, & Reich, 2007;Keele et al, 2009;Langergraber, Mitani, & Vigilant, 2007;Moeller et al, 2016;Rudicell et al, 2010;Santiago et al, 2003;Vigilant, Hofreiter, Siedel, & Boesch, 2001;Walker et al, 2017;Wroblewski et al, 2015). However, traditional genotyping methods are cumbersome, imprecise and investigator/platform dependent, due to the use of capillary electrophoresis to determine the length of STR loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, microsatellite analyses have been an integral part of studies of wild chimpanzees, providing insight into their evolution, population genetics, behavior, disease association and social structure (Barbian et al, 2018;Becquet, Patterson, Stone, Przeworski, & Reich, 2007;Keele et al, 2009;Langergraber, Mitani, & Vigilant, 2007;Moeller et al, 2016;Rudicell et al, 2010;Santiago et al, 2003;Vigilant, Hofreiter, Siedel, & Boesch, 2001;Walker et al, 2017;Wroblewski et al, 2015). However, traditional genotyping methods are cumbersome, imprecise and investigator/platform dependent, due to the use of capillary electrophoresis to determine the length of STR loci.…”
Section: Discussionmentioning
confidence: 99%
“…To reliably monitor the spread of SIVcpz in all three Gombe communities, we verified the individual origin of each fecal sample by microsatellite analysis at eight polymorphic STR loci. Thus, most Gombe chimpanzees have been repeatedly genotyped, resulting in a consensus genotype that has been used for paternity and kinship determinations, immunogenetics, microbiome analyses and behavioral studies (Barbian et al, 2018;Keele et al, 2009;Moeller et al, 2016;Rudicell et al, 2010;Santiago et al, 2003;Walker et al, 2017;Wroblewski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Disruption to the gut microbiota can therefore deleteriously affect host fitness by way of eliminating these beneficial functions. For example, immunocompromised individuals often display an altered gut microbiota (Lozupone et al, 2013;Moeller et al, 2013), which in some cases may contribute to systemic infection and host mortality (Barbian et al, 2018). Although the effects of temperature-induced changes in the gut microbiota on host colonization resistance have not been established, several recent lines of evidence suggest that disruption of animal gut microbiota by temperature may reduce the resistance of hosts to invasion and colonization by microorganisms with pathogenic qualities.…”
Section: Colonization Resistancementioning
confidence: 99%
“…Several studies suggested that enteric virome might be in primates found increased [42,43]. This implies that selected enteric virome metrics might be utilized as markers of the disease progression/remission, and also be exploited for evaluation of novel therapies and vaccine approaches.…”
Section: Enteric Virome and Gut Dysbiosismentioning
confidence: 99%